Traditional Food, Health, and Diet Quality in Syilx Okanagan Adults in British Columbia, Canada - Blanchet, Rosanne (Nutrients, 2020)
In Canada, store-bought food constitutes the majority of First Nations (FN) people’s diets; however, their traditional foods (TF; wild fish, game, fowl, and plants) remains vital for their health. This study compares health indicators and diet quality among 265 Syilx Okanagan adults according to whether or not they reported eating TF during a 24-h dietary recall. Three methods assessed diet quality: nutrient intakes and adequacy, Healthy Eating Index (HEI-C), and contributions of ultra-processed products (UPP) to %energy using the NOVA classification. Fifty-nine participants (22%) reported eating TF during the dietary recall; TF contributed to 13% of their energy intake. There were no significant differences in weight status or prevalence of chronic disease between TF eaters and non-eaters. TF eaters had significantly higher intakes of protein; omega-3 fatty acids; dietary fibre; copper; magnesium; manganese; phosphorus; potassium; zinc; niacin; riboflavin; and vitamins B6, B12, D, and E than non-eaters. TF eaters also had significantly better diet quality based on the HEI-C and the %energy from UPP. Findings support that TF are critical contributors to the diet quality of FN individuals. Strength-based FN-led interventions, such as Indigenous food sovereignty initiatives, should be promoted to improve access to TF and to foster TF consumption.